Assessment of Plasma Selenium-Binding Protein-1 Level in Geriatric Population - Dewi, Annisa F.; Dwipa, Lazuardhi; Lesmana, Ronny (Pharmacology and Clinical Pharmacy Research)
Geriatric physiologically undergoes aging process that can cause decreasing cell functionand increasing risk of degenerative diseases caused by the accumulation of reactive oxygenspecies (ROS) in the body. Selenium (Se) is an antioxidant, which is needed for maintainingthe balance of ROS. The aim of this study was to observe the selenium-binding protein(SELENBP1) level in relation with the geriatric patients charcateristics including sex, age,body mass index (BMI), activity of daily living (ADL), instrumental activity of daily living(IADL), cognitive function, nutrition, depression, and insomnia status. The study usedcross-sectional quantitative descriptive study design on 14 geriatric patients in Geriatric OutpatientsClinics, at a hospital in Bandung. The data was obtained by interviewing the patientsand then blood samples were taken. The analysis of SELENBP1 was done using ELISA kit.The average level (SD) of SELENBP1 from all of the characteristics group was 2.68 (0.69)ng/ml. The highest SELENBP1 level was identified in female geriatric patients and followedby male and pre-obese groups. The lowest SELENBP1 level was identified in geriatric patientsaged 70-79 years.Keywords: elderly, SELENBP1, selenium.